速开弹簧夹紧装置设计 - 薛培军; 游煌煌; 吴文剑; 曹志强 (Jixie chuandong)
Clamping device is widely used in many machines. We use of the optimization to design a rapidly loosen springs of clamping device with springs fabric properly. By application practically, it is not only reduced the weight of the machine, but also increased working efficiency obviously.